The study of cell homeostasis state of the gastric mucosa of rats on model of rheumatoid arthritis , treatment with ibuprofen and its combination with vinboron - F. V. Hladkykh; N. H. Stepaniuk; S. V. Vernihorodskyi (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Introduction. The use of NSAIDs in clinical practice is known for a significant reduction of side effects risks, among which the largest share of toxic effects on the digestive system. At the same time, the attention of researchers is increasingly payed to a specific syndrome associated with application of this group of drugs - NSAIDs gastropathy, with necrosis of epithelial cells as a possible morphological substrate. However, as the recent studies have shown, necrosis is not the only, but also is not the main cause of cell death. Apoptosis, the programmed cell death, is observed more often than necrosis. Besides, ulcerogenesis problem is closely linked to the ability of the gastric mucosa epithelium to adequate regeneration. This necessitates a search for the ways to correct the effect of non-steroidal antiphlogistics on the processes of apoptosis and proliferous activity of epithelial cells of the gastric mucosa. Materials and methods. Immunohistochemical studies were performed on paraffin sections using streptavidin-biotin method ("DAKO", Denmark; LSAB2 Systems, HRP). Antigen unmasking was performed in citrate buffer pH 6.0. Mice`s and rabbit`s monoclonal antibodies were used as the primary antibodies. The cell nuclei were colored with Mayer's hematoxylin for 15-60 seconds. Condition gastric epithelial proliferative activity was studied using a mouse monoclonal antibody to nuclear antigen Ki-67 ("DAKO", MIB-1 clone, Denmark) as a sensitive marker of proliferation by T. Scholzen. To characterize the activity of apoptosis the expression of CPP32 (caspase-3) in the gastric mucosa was examined, using semiquantitative rating scale color intensity of 0 (none) - no positive reactions in cells, 1 (weak) - up to 30% of the cells reacted positively 2 (moderate) - 31-60%, and 3 (strong) - 60% more stained cells.Results and Discussion. Analysis of the results of immunohistochemical expression of Ki-67 and CPP32 showed that the basis of gastroprotective effect of vinboron with ibuprofen-induced gastropathy in rats with adjuvant arthritis is its ability to enhance the regenerative properties of the gastric epithelium by restoring the proliferative activity. In addition vinboron is able to inhibit apoptosis induced by ibuprofen epithelial cells of the stomach, which helps to maintain cellular homeostasis of the gastric mucosa.